1990
DOI: 10.1016/0038-1098(90)90045-d
|View full text |Cite
|
Sign up to set email alerts
|

An exafs study of the cluster molecule Au55(PPh3)12Cl6

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 14 publications
5
31
0
Order By: Relevance
“…For a full analysis, it was also necessary to include an f-factor due to the motion of the whole gold cluster. By using instead the Au-Au interatomic distance obtained from EXAFS [5]- [8] and the spring constant corrected for the higher binding energy found by calorimetry [9], the agreement between calculated and measured 8/~'s has now been improved to within 2%. Using the interatomic distance of bulk gold and the spring constant determined from the bulk modulus of gold, the original calculated 8E's were about 10% smaller than the experimental values.…”
Section: Au Msssbauer Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…For a full analysis, it was also necessary to include an f-factor due to the motion of the whole gold cluster. By using instead the Au-Au interatomic distance obtained from EXAFS [5]- [8] and the spring constant corrected for the higher binding energy found by calorimetry [9], the agreement between calculated and measured 8/~'s has now been improved to within 2%. Using the interatomic distance of bulk gold and the spring constant determined from the bulk modulus of gold, the original calculated 8E's were about 10% smaller than the experimental values.…”
Section: Au Msssbauer Spectroscopymentioning
confidence: 99%
“…The icosahedral structural type is the usual one for gold cluster compounds containing fewer metal atoms, typically 11 or 13; their bonding is dominated by covalent radial interactions to the single centrM gold atom [4]. For example, EXAFS measurements show a single nearestneighbour Au-Au distance in Auss(PPh~)12Cls, proving that the cluster cannot have an icosahedral structure [5,6,7,8]. For example, EXAFS measurements show a single nearestneighbour Au-Au distance in Auss(PPh~)12Cls, proving that the cluster cannot have an icosahedral structure [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors [46,47,54] have published good quality L 3 edge EXAFS for Au 55 and Au 11 clusters stabilised by a variety of organic ligands. These studies showed that the fcc structure of bulk Au was retained in the clusters, but with a contraction in the nearest neighbour distance of 0.05 -0.1 Å for Au 55 and up to 0.2 Å for Au 11 .…”
Section: Catalytic Metal Clustersmentioning
confidence: 99%
“…The famous Schmid cluster, Au 55 (PPh 3 ) 12 Cl 6 [43] was one of the first size-specific Au NCs studied with XAS in the 1990s [44][45][46]. Au L 3 -edge EXAFS fitting results from a few studies suggested the Au core is likely cuboctahedral instead of icosahedral.…”
Section: Introduction To Gold Nanoclustersmentioning
confidence: 99%